2021
DOI: 10.11591/ijere.v10i3.21127
|View full text |Cite
|
Sign up to set email alerts
|

Roles of career maturity mediating the effects of locus of control and socioeconomic status on career readiness

Abstract: <span>This study aimed to analyze students' readiness for careers out of their professions by considering the effect of locus of control and socioeconomic status. Career maturity acted as the variable intervening. The quantitative method was chosen to test the hypothesis. A total of 80 students were selected to be respondents based on purposive sampling. Model testing was done by using PLS-SEM. The findings of this study found that the locus of control influenced student career readiness. Conversely, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…The findings of this study suggest that students with a higher level of locus of control, particularly those with a strong internal locus of control, are more likely to demonstrate higher levels of work readiness. This aligns with previous research conducted by Setiawan & Yusnaini (2021), Jayanti et al (2021), Sholikah &Muhyadi (2021), andCholik et al (2022). These studies also reported a positive and significant influence of locus of control on work readiness.…”
Section: Modelsupporting
confidence: 91%
“…The findings of this study suggest that students with a higher level of locus of control, particularly those with a strong internal locus of control, are more likely to demonstrate higher levels of work readiness. This aligns with previous research conducted by Setiawan & Yusnaini (2021), Jayanti et al (2021), Sholikah &Muhyadi (2021), andCholik et al (2022). These studies also reported a positive and significant influence of locus of control on work readiness.…”
Section: Modelsupporting
confidence: 91%
“…In general, strategies to enhance career readiness have been identified. Indonesia Career readiness among low-income Muslim students [16] Malaysia The mediating role of career decision self-efficacy on the relationship of career emotional intelligence and self-esteem with career adaptability among university students [17] South Korea The mediating role of entrepreneurial mindset between intolerance of uncertainty and career adaptability [18] Indonesia Roles of career maturity mediating the effects of locus of control and socioeconomic status on career readiness [19] China Proactive personality and career adaptability of Chinese female pre-service teachers in primary schools: the role of calling [1] UK Increasing students' career readiness through career guidance: measuring the impact with a validated measure [20] Indonesia…”
Section: Resultsmentioning
confidence: 99%